OPTIMALISASI PENGGUNAAN SCRIBUS UNTUK DESAIN GRAFIS EDITORIAL MAHASISWA TEKNOLOGI REKAYASA MULTIMEDIA GRAFIS - Yunus Anis, Yunus Anis; Hersatoto Listiyono; Sri Mulyani; Sunardi; Vici Tiara Anjarsari (Servis : Jurnal Pengabdian dan Layanan kepada Masyarakat, 2025)
Editorial graphic design is a vital skill in the creative industry, especially for producing magazines, brochures, and other publication media. However, the high cost of commercial software licenses such as Adobe InDesign poses a major barrier for students of the Multimedia Graphic Engineering Technology (TRMG) study program in developing editorial design competencies. This community service activity aims to optimize the use of Scribus, an open-source desktop publishing (DTP) software, as a legal and functional alternative for editorial design. The program involved an initial needs assessment, module development, a three-day intensive training, hands-on practice, and pre- and post-training evaluations. The results show a significant improvement in students’ understanding and skills in creating digital publication layouts using Scribus. Additionally, the quality of editorial designs produced by participants improved in terms of visual composition and content structure. This initiative also promotes the ethical and professional use of free-license software. It is expected that Scribus can be integrated into editorial design courses within the TRMG curriculum and support the ongoing development of student portfolios.